Williams Syndrome with a “Twist” - Despoina Maritsi; Lydia Kossiva; George Vartzelis (Case Reports in Medicine)
Williams syndrome is a rare genetic condition with multisystemic involvement, caused by a microscopic deletion in the chromosome band 7q11.23. We describe the first case of a toddler with Williams syndrome who developed Benign Paroxysmal Torticollis (BPT), a benign dystonic disorder of unknown aetiology.